Women Workers in the Indonesian Labor Market: Inevitable Marginalization - Poppy - Ismalina (Yayasan Jurnal Perempuan, 2018)
By conducting descriptive statistical analysis and the establishment of two econometric models, this study proves that the marginalization of women in the Indonesian labor market still occurs even though the quality of Indonesian women from the level of education and work participation is increasing. The phenomenon of marginalization of women is characterized by 1) the wage gap due to gender differences, namely the wages received by female workers are lower than male workers for all types of work; 2) the chances of men to find work are far higher than women in the Indonesian labor market. The study concludes that the wage gap due to gender differences is not due to competition in the labor market but rather due to the assumption that working women are secondary and supplementary breadwinners in their households, and the role that they can be play is only an extension of their domestic role. Thus, the main cause of the marginalization of women in the labor market is the low awareness of gender equality, something which has already taken root in Indonesia.